Empiric antibiotic therapy in a child with cancer and suspected septicemia - Desiree Caselli; Olivia Paolicchi (MDPI AG, 2012)
Improved outcome in the treatment of in childhood cancer results not only from more aggressive and tailored cancer-directed therapy, but also from improved supportive therapy and treatment of life-threatening infectious complications. Prompt and aggressive intervention with empiric antibiotics has reduced the mortality in this group of patients. Physical examination, blood tests, and blood cultures must be performed, and antibiotic therapy must be administered as soon as possible. Beta-lactam monotherapy, such as piperacillin-tazobactam or cefepime, may be an appropriate empiric therapy of choice for all clinically stable patients with neutropenic fever. An anti-pseudomonal beta-lactam antibiotic plus gentamicin is recommended for patients with systemic compromise.